People with insomnia: experiences with sedative hypnotics and risk perception. (3rd August 2015) - Cheung, Janet M. Y.; Bartlett, Delwyn J.; Armour, Carol L.; Ellis, Jason G.; Saini, Bandana
Abstract: Background: Sedative hypnotics form an important part of managing insomnia and are recommended for short‐term use. It is standard practice for clinicians to inform the patient to use medications only 'when required', but the use of these medications is often chronic. Little is known about the impact of standard labelling/instructions on promoting appropriate medication use for managing insomnia. Objective: To explore patient medication‐taking beliefs, experiences and behavioural practices relating to the use of pharmacological/complementary sleep aids for insomnia. Setting and Participants: Specialist sleep/psychology clinics and the general community in Sydney, Australia. Method: Semi‐structured interviews were conducted with 51 people with insomnia using a schedule of questions to gauge their experiences, beliefs and current practices relating to insomnia medication use. Interviews were audio‐recorded, transcribed verbatim and subjected to Framework Analysis to identify emergent themes. Results: Participants held distinctive views about the safety and efficacy of complementary and pharmacological agents but do not intuitively turn to medications to resolve their sleep complaint. Medication use was affirmed through tangible medication‐taking cues due to the ambivalence in current instructions and labelling. Practices such as dosage modification, medication substitution and delaying medication use might be important drivers for psychological dependence. Conclusion: Current labelling and instructions do not necessarily promote the quality use of sedative hypnotics due to the variability in patient interpretations. Clarifying the timing, quantity and frequency of medication administration as well as insomnia symptom recognition would play a significant role in optimizing the role of pharmacotherapy in the management of insomnia.